Pelatihan Mitigasi Bencana Alam Gempa Bumi Pada Siswa Sekolah Dasar Negeri Senden 2 Kecamatan Ngasem Kab Kediri Jawa Timur: Earthquake Natural Disaster Mitigation Training for Senden 2 State Elementary School Students, Ngasem District, Kediri Regency, East Java - Suwardianto, Heru; Triyoga, Akde; Febrijanto, Yoyok (Chakra Brahmanda Lentera Institute, 2023)
Earthquakes can cause many victims if capacity building is not carried out in vulnerable communities. Elementary school (SD) students need to be informed about earthquake preparedness so that they continue to be prepared for earthquake alerts. This study aims to analyze the effect of earthquake natural disaster mitigation training on Senden 2 Elementary School students, Kediri District, East Java. The method used is training with a pre post test design approach. The population is students of SDN Senden 2. The variables measured are knowledge and skills. The training involved 35 elementary school students consisting of grade IV students. The instrument used is the Knowledge Questionnaire. The intervention provided is disaster management training in the classroom and outside the classroom. Based on the results of the study it was found that the results of the pre test were mostly obtained by respondents having insufficient knowledge about earthquake disaster mitigation as many as 23 respondents (65.71%), while the results of the post test were mostly obtained by respondents having sufficient knowledge about earthquake natural disaster mitigation as many as 19 respondents (54.29%). The statistical test results with the Wilcoxon test obtained p value = 0.001 (a <0.05) which means that there is an effect of earthquake natural disaster mitigation training on knowledge of students at SDA Negeri Senden 2, Kediri District, East Java. Earthquake disaster mitigation training must continue to be carried out to increase student awareness and reduce disaster victims due to unpredictable earthquakes. Keywords: Mitigation, Knowledge, Elementary School.